The Effect of Learning Styles and Class Management on Student Learning Outcomes in Accounting Subject at SMKN 1 Tinambung - ST Suabedah; Muhammad Azis; Sahade Sahade (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
This study aims to determine the effect style learning and management class to results Study eye student lesson accounting at SMKN 1 Tinambung . Variable in study This style learning and management class as variable free and results Study as variable bound . Population in study This is whole student major accounting at SMKN 1 Tinambung from class X up with class XII. Retrieval technique sample use technique taking sample saturated , that is take in a manner whole existing population that is as many as 90 students . Data collection techniques used is questionnaire and documentation . Data analysis technique used is analysis descriptive percentage , instrument test , assumption test classic , and hypothesis testing with use SPSS version 25 for windows . Based on data analysis performed so obtained equality multiple linear regression Y = 60.078 + 0.280X 1 + 0.385X 2 which means that If variable style learning and management class considered The same with zero , then variable results Study of 60.078. Besides That style learning and management class in a manner simultaneous influential positive and significant to results Study with significance 0.003 <0.05, style Study in a manner Partial influential positive and significant to results Study with level significance 0.011 <0.05, and management class in a manner Partial influential positive and significant to results Study with level significance 0.044 <0.05. From the results coefficient determination (R 2 ) of 0.416. this means that influence style learning and management class to results Study by 41.6%. Temporary coefficient style learning (r 2 ) of 18.6% and yield coefficient management class (r 2 ) of 23.6%. With so , management class more dominant influence results Study student , with thereby hypothesis can accepted .